2017
DOI: 10.1016/j.amjmed.2016.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and Causes of Long-Term Mortality in Elderly Patients with Acute Venous Thromboembolism: A Prospective Cohort Study

Abstract: Elderly patients with acute venous thromboembolism have a substantial long-term mortality, and several factors, including polypharmacy and a low physical activity level, are associated with long-term mortality. Cancer, pulmonary embolism, infections, and bleeding are the most common causes of death in the elderly with venous thromboembolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 31 publications
3
84
1
Order By: Relevance
“…Several studies have shown that D-dimer is a good diagnostic test for diverse thrombotic conditions, such as ischemic stroke (Nezu et al, 2018), venous thromboembolism (Faller et al, 2017), pulmonary embolism (van der Hulle et al, 2013), and aortic dissection (Mussa et al, 2016). In addition to its high diagnostic value for thrombotic disease, recent studies have also reported its relationship with short-term and long-term prognosis of these diseases (Kim et al, 2015;Vele et al, 2016;Faller et al, 2017). Additionally, several studies have shown an association in the general population (Di Castelnuovo et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that D-dimer is a good diagnostic test for diverse thrombotic conditions, such as ischemic stroke (Nezu et al, 2018), venous thromboembolism (Faller et al, 2017), pulmonary embolism (van der Hulle et al, 2013), and aortic dissection (Mussa et al, 2016). In addition to its high diagnostic value for thrombotic disease, recent studies have also reported its relationship with short-term and long-term prognosis of these diseases (Kim et al, 2015;Vele et al, 2016;Faller et al, 2017). Additionally, several studies have shown an association in the general population (Di Castelnuovo et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…D-dimer, a specific degradation product of cross-linked fibrin, represents the coagulation and fibrinolytic system activation (Suzuki et al, 2009). It is now commonly used in the diagnosis of pulmonary embolism (van der Hulle et al, 2013), deep vein thrombosis (Faller et al, 2017), acute coronary syndrome (Bayes-Genis et al, 2000), and acute aortic dissection (Akutsu et al, 2005;Suzuki et al, 2009;Shao et al, 2014). For acute aortic dissection, the mechanisms of coagulation and fibrinolytic system activation might be (1) coagulant material from the aortic wall released into the circulation and (2) an accumulation of clotting factors at the site of the lesion, secondary to the local exposition of tissue factors from the torn arterial wall (Ten Cate et al, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…Data from cohort studies indicate that risk factors associated with an increased risk of all-cause death, beyond cancer and presentation as severe PE, include age (hazard ratio [HR]: 1.32 per decade), low physical activity level (HR: 1.92), diabetes mellitus (HR: 1.50), anemia (HR: 1.48), and polypharmacy (HR: 1.41). 30 Therefore, from a global healthcare perspective, measures to improve survival after VTE, in addition to improvement in anticoagulant therapy, should include an integral patient management, streamlining the treatment of other relevant comorbidities, applying proven measures to reduce global CV risk, and promoting healthy lifestyles. 31,32 With respect to deaths by type of anticoagulant we found that in comparison with warfarin, the NOAC did not reduce all-cause mortality, CV mortality, or non-CV mortality.…”
Section: Discussionmentioning
confidence: 99%
“…35 Finally, our metaanalysis is based on data from selected populations from clinical trials, 36 but causes of death are consistent with those reported in unselected populations in standard practice. 30…”
Section: Discussionmentioning
confidence: 99%
“…Faller and colleagues also performed a prospective multicenter cohort study in older patients, in which 991 patients with acute venous thromboembolism (VTE) and aged >65 years were followed up for a median period of 30 months. 39 Overall, 206 patients (21%) died during follow-up. The frequency of hs-cTnT concentrations above the 99th percentile URL (i.e., >14 ng/L) was 69% compared with 46% in those who survived (p < 0.001).…”
Section: Review Of Clinical Evidence Of the Role Of Hs-ctn In Pulmonamentioning
confidence: 99%